2020
DOI: 10.1177/1559325820936170
|View full text |Cite
|
Sign up to set email alerts
|

Does Green Tea Induce Hormesis?

Abstract: Green tea, and its principal constituent (–)-epigallocatechin-3-gallate (EGCG), are commonly shown to induce biphasic concentration/dose responses in a broad range of cell types, including non-tumor cells, and tumor cell lines. The most active area of research dealt with an assessment of neural cells with application to neurodegenerative diseases such as Parkinson’s disease and Alzheimer’s disease cell models, often using preconditioning experimental protocols. The general findings demonstrate EGCG-induced hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 97 publications
1
20
0
Order By: Relevance
“…This experiment demonstrates the possible hormetic effect of polyphenols/H 2 O 2 in cell signaling and its possibility to also act as a Distress compound. Most recently, just during the preparation of this review, Calabrese et al [141], by searching hormesis effects of polyphenols, confirmed our previous data and conclusions [13].…”
Section: Hormesis/eustress and Distress By Polyphenolssupporting
confidence: 83%
“…This experiment demonstrates the possible hormetic effect of polyphenols/H 2 O 2 in cell signaling and its possibility to also act as a Distress compound. Most recently, just during the preparation of this review, Calabrese et al [141], by searching hormesis effects of polyphenols, confirmed our previous data and conclusions [13].…”
Section: Hormesis/eustress and Distress By Polyphenolssupporting
confidence: 83%
“…metic dose response when sufficient conditioning doses are used in the experiment [5][6][7] rmetic dose responses are general, being independent of biological model, inducing agen point, level of biological organization, and mechanism [8]. A series of recent publications hav umented hormetic dose responses in the biomedical literature for curcumin [9], Ginkgo bilob ], and green tea [11]. The present findings show that ginseng-induced hormetic effects are als monly reported that are broadly generalizable, affecting numerous organ systems, cell types, an points, showing capacity to induce acquired resilience for various durations, within multiple an erse experimental settings, with particular research focus directed toward neuroprotective effect bles 1-3).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the inactivity of green tea polyphenols against superoxide free radicals may be due to high doses used, which resulted in a pro-oxidant toxic effect [ 252 ]. The main constituent of green tea, (−)-epigallocatechin-3-gallate, revealed biphasic dose-response on a broad range of cell types (non-tumor and tumor cell lines) [ 253 ].…”
Section: Herbal Infusion Contradictory Effectsmentioning
confidence: 99%